1995
DOI: 10.1016/0168-6445(95)00021-6
|View full text |Cite
|
Sign up to set email alerts
|

Virulence factors of Actinobacillus actinomycetemcomitans relevant to the pathogenesis of inflammatory periodontal diseases

Abstract: There is strong evidence implicating Actinobacillus actinomycetemcomitans as the causative agent of localised juvenile periodontitis (LJP), a disease characterised by rapid destruction of the tooth-supporting tissues. This organism possesses a large number of virulence factors with a wide range of activities which enable it to colonise the oral cavity, invade periodontal tissues, evade host defences, initiate connective tissue destruction and interfere with tissue repair. Adhesion to epithelial and tooth surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
76
0
3

Year Published

2000
2000
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(81 citation statements)
references
References 81 publications
2
76
0
3
Order By: Relevance
“…[3][4][5][6][7][8][9][10] This bacterium expresses several putative virulence factors which enable it to colonize the oral cavity, invade periodontal tissues and evade host defenses. 11 Additionally, different serotypes of A. actinomycetemcomitans have been shown to be associated with periodontal health and disease. 12,13 Chronic periodontitis may begin in adolescence as a slowly progressing disease that becomes clinically significant in the mid-30 s and continues throughout life.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10] This bacterium expresses several putative virulence factors which enable it to colonize the oral cavity, invade periodontal tissues and evade host defenses. 11 Additionally, different serotypes of A. actinomycetemcomitans have been shown to be associated with periodontal health and disease. 12,13 Chronic periodontitis may begin in adolescence as a slowly progressing disease that becomes clinically significant in the mid-30 s and continues throughout life.…”
Section: Introductionmentioning
confidence: 99%
“…Actinobacillus actinomycetemcomitans is a gramnegative bacterium that is regarded as a member of the microflora of dental plaque and, therefore, may play a role in chronic inflammatory periodontal disease (CIPD) [1,2]. Evidence has shown that the numbers of this micro-organism are increased in patients with periodontal disease, especially those with early-onset periodontitis [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…These include endocarditis, meningitis, osteomyelitis, s.c. abscesses, endophthalmitis, and periodontal disease (1)(2)(3)(4)(5)(6)(7). Although the pathogenic mechanism(s) by which A. actinomycetemcomitans acts to cause disease is not known, it has been shown to produce several potential virulence factors capable of facilitating colonization, destroying host tissue, inhibiting tissue repair, and interfering with host defenses (reviewed in Ref.…”
mentioning
confidence: 99%